2019
DOI: 10.1016/j.omtn.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A Chymase Inhibitory RNA Aptamer Improves Cardiac Function and Survival after Myocardial Infarction

Abstract: We have reported that mast cell chymase, an angiotensin II-generating enzyme, is important in cardiovascular tissues. Recently, we developed a new chymase-specific inhibitory RNA aptamer, HA28, and we evaluated the effects of HA28 on cardiac function and the mortality rate after myocardial infarction. Echocardiographic parameters, such as the left ventricular ejection fraction, fractional shortening, and the ratio of early to late ventricular filling velocities, were significantly improved by treatment with HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Interestingly, combined inhibition of both chymase and ACE was superior to ACE-I alone, as was evident by improved cardiac function and cardiac remodeling in rodents ( 58 ). In line with these findings, clinical studies demonstrated that an inhibitor of chymase-specific RNA aptamer improved cardiac function in patients following myocardial infarction ( 72 ).…”
Section: Chymase and Covid-19mentioning
confidence: 74%
“…Interestingly, combined inhibition of both chymase and ACE was superior to ACE-I alone, as was evident by improved cardiac function and cardiac remodeling in rodents ( 58 ). In line with these findings, clinical studies demonstrated that an inhibitor of chymase-specific RNA aptamer improved cardiac function in patients following myocardial infarction ( 72 ).…”
Section: Chymase and Covid-19mentioning
confidence: 74%
“…We also observed that the specific chymase inhibitor TY-51469 showed a reduction of mast cell and MMCP-4-positive cell numbers. Numerous studies have demonstrated that chymase inhibitors can reduce mast cell numbers in various experimental models [ 38 , 39 , 40 , 41 ]. Chymase is known to enzymatically cleave the inactive membrane-bound form of stem cell factor (SCF) to the active form of SCF, and the activated SCF stimulates the development and proliferation of mast cells, resulting in increased mast cell numbers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the aptamer also blocked tumor cell dissemination in mice, providing a new insight for miRNA-based therapeutic development. In a similar study, Jin et al (2019) developed an RNA aptamer (HA28) towards chymase, which plays an essential role in the regulation of Ang II in cardiovascular tissues [ 71 ]. The effect of HA28 aptamer was evaluated on the cardiovascular tissues, after myocardial infarction.…”
Section: Aptamers As Therapeutic Agentsmentioning
confidence: 99%